El proceso de enseñanza – aprendizaje de la Matemática en los estudiantes de segundo grado de educación básica de la Unidad Educativa “Mulaló”, año lectivo 2021-2022. - Velastegui Sarabia, Dora Cecilia (2022)
The present investigation is focused on the resolution of the following problem: How to improve the teaching-learning process of Mathematics in the second grade students of basic education of the Mulaló Educational Unit?; for which it has been proposed as a general objective, to improve the teaching-learning process of Mathematics through the implementation of innovative methodologies aimed at strengthening the learning of students in the second grade of basic education of the Mulaló Educational Unit. The methodology used is developed under the qualitative-quantitative approach, methods and techniques have been used such as: inductive-deductive method, observation, interview guide, survey and analysis of the products of the activity, which provided the possibility of make an initial diagnosis associated with the educational processes in the institution and at the same time allowed conclusions to be reached, which show that the application of a guide of activities framed in innovative methodologies strengthens knowledge through active parti cipation, achieving in students the ability to achieve knowledge through the autonomous construction of the same, with continuous intervention in the execution of each of the actions developed in a didactic and creative way. Regarding the results of the application of the guide based on the flipped classroom method, it is highlighted that the Mathematics teaching-learning process reached a significant percentage in the achievement of skills due to the innovative activities proposed in an active way, which, piqued the interest of every student.